Standardized multilevel transition program: Does it affect renal transplant outcome?. (11th August 2015) - Weitz, Marcus; Heeringa, Saskia; Neuhaus, Thomas J.; Fehr, Thomas; Laube, Guido F.
Abstract The transfer of renal transplant patients from pediatric to adult care is a crucial step with a high risk of subsequent graft loss. Therefore, the transition should be a thoroughly planned, well‐designed and multidisciplinary process focused on the individual patient. Our pediatric nephrology department introduced a structured step‐by‐step transition program supported by a multidisciplinary team of health professionals. The purpose of our study was to determine the effects of the transition program on eGFR and number of ARs in comparison to a group without a transition program at one and three yr after transfer. We conducted a single‐center retrospective cohort study of renal transplant patients prior to and after the introduction of the transition program. Multiple regression analysis revealed a significantly lower decline of eGFR in the group with transition program (−11.3 ± 44 mL/min/1.73 m2) compared to the group without transition program (−28.4 ± 33 mL/min/1.73 m2) at three yr after transfer. The number of AR episodes significantly decreased from 34.6% in the group without transition program to 9.1% in the group with transition program. The standardized multilevel transition program seems to have significant positive effects on eGFR and number of AR episodes in renal transplant patients.